Suicide prevention in Bangladesh: The role of family - S M Yasir Arafat; Tamkeen Saleem; Todd M. Edwards; Syeda Ayat‐e‐Zainab Ali; Murad M. Khan (Brain and Behavior, 2022)
Abstract Background Suicide is a public health problem that gets little attention in Bangladesh especially in prevention aspects. Recent studies revealed that a significant portion of risk factors is closely related to family events. However, potential prevention strategies considering the family structure and involving family dynamics of Bangladesh have not been discussed. Objectives We aim to highlight areas of family vulnerability and resilience when the threat of suicide is present, as well as the potential roles of family in suicide prevention in Bangladesh. Methods We conducted a thorough narrative and focused literature search and synthesized evidence based on available articles discussing suicidality and family dynamics in Bangladesh. Results Risk factors for suicide prevailing in the family have been organized, and several strategies for coping with family risk factors, including marital discord and family conflict have been proposed for testing empirically. Conclusions The family has an important role to play in suicide prevention in Bangladesh. However, potential prevention strategies and their effectiveness have been untapped in the country. Studies are warranted to test the effectiveness of the proposed strategies.